Primary health care, access to legal abortion and the notion of ideal victim among medical practitioners: The case of Chile - Casas, Lidia C.; Álvarez, Juan J.; Vivaldi, Lieta V.; Montero, Adela R.; Bozo, Natalia; Babul, Jorge (Frontiers in Psychology, 2022)
In 2017, Chile enacted new legislation allowing access to legal abortion on three grounds, including rape. This article summarizes a qualitative, exploratory study that examined the role of primary healthcare services in the treatment of rape-related cases in order to identify challenges and strengths in accessing legal abortion. The relevant data was collected through 19 semi-structured interviews conducted with key informants. The angry legislative debate that preceded enactment of the 2017 abortion bill evidenced the presence of strong biases against victims of sexual violence. At the time, abortion opponents sought, inter alia, to discredit women who report rape, arguing that such claims would be misused to secure illicit abortions. In actual fact, however, rape has turned out to be the least used of all grounds for abortion, with girls and teens making up the smallest group of seekers. This article presents our findings on rape-related issues, notably the biases and shortcomings of medical practitioners regarding the new abortion law. We noted with concern their failure to screen for sexual violence and propensity to stigmatize the victims, a phenomenon that becomes exacerbated when it involves particularly vulnerable populations, such as girls and women who are poor, homeless, migrant, or who abuse alcohol or drugs. We further noted that prevalent stereotypes based on the notion of the ideal victim can revictimize girls and women and work to defeat the intent of the law. In Chile, the primary healthcare system is a key point of entry for abortion. In this highly charged arena, however, lack of political will, compounded by the COVID-19 pandemic, have kept health care practitioners from undergoing timely, gender-sensitive training on the new law, a key requirement for ensuring dignified care and respect for women’s rights. We conclude that if government policy is to prevent multiple, intersectional discrimination, it must recognize the diversity of women and adapt to their specific contexts and singularities.